Axonal pathology differentially affects human Purkinje cell subpopulations in the essential tremor cerebellum - James Widner; Phyllis L. Faust; Elan D. Louis; Hirofumi Fujita (Proceedings of the National Academy of Sciences, 2025)
The cerebellar cortex is organized into discrete regions populated by molecularly distinct Purkinje cells (PCs), the sole cortical output neurons. While studies in animal models have shown that PC subtypes differ in their vulnerability to disease, our understanding of human PC subtype and vulnerability remains limited. Here, we demonstrate that human cerebellar regions specialized for motor vs. cognitive functions (lobule HV vs. Crus I) contain distinct PC populations characterized by specific molecular and anatomical features, which show selective vulnerability in essential tremor (ET), a cerebellar degenerative disorder. Using a known PC subtype marker, neurofilament heavy chain (NEFH), we found that motor lobule HV contains PCs with high NEFH expression, while cognitive lobule Crus I contains PCs with low NEFH expression in postmortem samples from healthy controls. In the same cerebella, PC axons in lobule HV were 2.2-fold thicker than those in Crus I. Across lobules, axon caliber positively correlated with NEFH expression. In ET cerebella, we identified motor lobule-specific PC axon pathology with a 1.5-fold reduction in caliber and increased axon variability in lobule HV, while Crus I axons were unaffected. Tremor severity and duration in ET correlated with axon diameter variability selectively in lobule HV PCs. Given that axonal caliber is a major determinant of neural signaling capacity, our results 1) suggest that disrupted cerebellar corticonuclear signaling is occurring in ET, and 2) provide evidence of region-specific PC populations in the human cerebellum and offer insight into how different PC subpopulations may contribute to the pathophysiology of cerebellar degeneration.